Reviews of Physiology, Biochemistry and Pharmacology, Vol. 167 - Nilius, Bernd; Gudermann, Thomas; Jahn, Reinhard; Lill, Roland; Offermanns, Stefan; Petersen, Ole H. (Reviews of Physiology, Biochemistry and Pharmacology, 2014)
Contents R. Nassini, S. Materazzi, S. Benemei, and P. Geppetti: The TRPA1 Channel in Inflammatory and Neuropathic Pain and Migraine D. Lim, V. Ronco, A.A. Grolla, A. Verkhratsky, and A.A. Genazzani: Glial Calcium Signalling in Alzheimer's Disease J. Lazniewska and N.Weiss: The "Sweet" Side of Ion Channels E.E. Tevoufouet, E.N. Nembo, M.Dibué-Adjei, J. Hescheler, F. Nguemo, and T. Schneider: Cardiac Functions of Voltage-Gated Ca2+ Channels: Role of the Pharmacoresistant Type (E-/R-Type) in Cardiac Modulation and Putative Implication in Sudden Unexpected Death in Epilepsy (SUDEP) .